Liber homo suo nomine utilem Aquiliae habet actionem: D. 9,2,13 pr. in context - Scott, H (Vandenhoeck and Ruprecht, 2014)
The contributions to this volume are concerned with the Roman law of antiquity in its broadest sense, covering both private and public law from the Roman Republic to the Byzantine era, including legal papyrology.